Reading Difficulties among Elementary Students in a Rural Area: A Qualitative Study - Karlina Karadila Yustisia; Dhia Lintang Eka Salsabila (Universitas Merdeka Malang, 2023)
This study investigates the factors that influence reading difficulties among elementary students in a rural area. Based on observations and interviews, the study reveals limited language skills due to the use of local dialects, impacting comprehension and decoding abilities. Phonetic awareness also requires improvement, with difficulties in recognizing and distinguishing letters. Cognitive deficiencies, particularly in working memory, affect reading comprehension. Some students display varying attentiveness, with some preferring activities like drawing, hindering engagement in reading tasks. The home literacy environment and parental involvement significantly influence reading proficiency. The absence of preschool education affects students' foundational literacy skills upon entering primary school. Recommendations include personalized approaches and early childhood education advocacy to enhance reading skills in rural students.